SPDT Switch with Defected Ground Structure for Time Division Duplex Switching in Wireless Data Communication System. - Shairi, Noor Azwan; Ahmad, Badrul Hisham; Abd Aziz, Mohamad Zoinol Abidin; Osman, Anuar Faidz (2011)
A design of single series and double shunt of single pole double throw (SPDT) switch with defected ground structure (DGS) is presented in this paper. SPDT switch is commonly used in a RF transceiver system in modern wireless data communication system to perform time division duplex (TDD) switching for transmit and receive operation. The implementation of DGS in this switch has reduced 35% of the transmission line length and thus, reducing the circuit board size. The performances of SPDT switch with DGS such as insertion loss and isolation are comparable with the normal SPDT switch.